2020
DOI: 10.1111/aji.13312
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid antibodies and extracellular vesicles in pregnancy

Abstract: Antiphospholipid antibodies (aPL) are autoantibodies that target phospholipid‐binding proteins, such as β2 glycoprotein I (β2GPI), and can induce thrombosis systemically, as well as increase the risk of obstetric complications such as recurrent miscarriage and preeclampsia. Due to the expression of β2GPI by placental trophoblasts, aPL readily target the maternal‐fetal interface during pregnancy and many studies have investigated the deleterious effects of aPL on placental trophoblast function. This review will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…Three subtypes of trophoblasts can be found in the human placenta: villous cytotrophoblasts, extravillous trophoblasts (EVT), and syncytiotrophoblasts (STB). The STB is a multinucleated single cell that covers the maternal-facing part of the placenta, plays a key role in the exchange of materials between mother and fetus, and is the main site of EV production and release into the maternal bloodstream [ 16 ]. In addition to conventional EVs, trophoblasts also release trophoblastic debris, which contain an average of 60 nuclei [ 44 ] and range in size from 20–500 μm [ 44 , 45 ].…”
Section: The Molecular Mechanisms Of Evs Contributing To Pregnancy Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…Three subtypes of trophoblasts can be found in the human placenta: villous cytotrophoblasts, extravillous trophoblasts (EVT), and syncytiotrophoblasts (STB). The STB is a multinucleated single cell that covers the maternal-facing part of the placenta, plays a key role in the exchange of materials between mother and fetus, and is the main site of EV production and release into the maternal bloodstream [ 16 ]. In addition to conventional EVs, trophoblasts also release trophoblastic debris, which contain an average of 60 nuclei [ 44 ] and range in size from 20–500 μm [ 44 , 45 ].…”
Section: The Molecular Mechanisms Of Evs Contributing To Pregnancy Disordersmentioning
confidence: 99%
“…EVs are normally released during pregnancy and carry or express increased levels of proinflammatory and procoagulant molecules on their surface, which contribute to enhanced inflammation and hypercoagulation during pregnancy [ 10 ]. Elevated levels of EVs and their distinct profile have been suggested to play a role in pregnancy disorders including PE and recurrent fetal loss, both of which are part of the clinical manifestations of obstetric APS [ 10 , 16 ]. The role of EVs in the pathology of obstetric APS has been investigated in vivo by isolating EVs from patient plasma and in vitro on EVs isolated from aPL-stimulated cell cultures.…”
Section: Extracellular Vesicles In Antiphospholipid Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, such surface adsorption adsorbs to cause changes in fibrinogen secondary structure, which may underlie in part the abnormal thrombus morphology caused by EVs. Mancy et al [ 93 ], studying the secretion of EVs by trophoblast cells, found that EVs are also enriched with a large number of antiphospholipid antibodies that target phospholipid-binding proteins such as beta-2-glycoprotein I (β2GPI), which in turn induces systemic thrombosis and increases the risk of obstetric complications such as recurrent miscarriage and pre-eclampsia. In addition, Nox-1 is enriched within PEVs, where they induce thrombosis while reverse-activating platelets by regulating ROS production downstream of glycoprotein VI (GPVI) [ 94 ].…”
Section: Activation Of the Coagulation System And Altered Fibrinolyti...mentioning
confidence: 99%
“…Recently, extracellular vesicles have been recognized as an important carrier of protein aggregates, miRNA, mRNA, lipids and apoptotic factors that may mediate inflammatory responses associated with PE pathophysiology (Schuster et al, 2021). Circulating extracellular vesicles exist in greater quantity in the plasma of PE subjects vs. normal pregnancy (Gilani et al, 2016;Tong et al, 2017;Schuster et al, 2021;Tong et al, 2021). Below, we will discuss the DAMPs that may be associated with the pathogenesis of PE (Figure 1).…”
Section: Damps: the Effectors Of Sterile Inflammation In Pementioning
confidence: 99%